A Duolingo-based English Language Skills Assessment: Through the Eyes of Vocational Students - Audi Yundayani; Muchlas Suseno; Elin Herlina (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2023)
The utilization of mobile-assisted language learning (MALL) enhances learning activities. As online learning modalities proliferate, Duolingo is becoming increasingly well-known but understudied as an English-learning assessment tool. This study explores the utilization of Duolingo as an English-learning assessment tool, specifically in the context of English for Specific Purposes (ESP) in Indonesia. Three Electromedical Engineering students were selected as participants, and semi-structured interviews were conducted to gather data. Thematic Analysis was employed to analyze the collected data. The findings revealed several positive impressions students had when using Duolingo as an English language skills assessment (ELSA) tool, including its engaging nature, facilitation of autonomous language skills assessment, provision of positive motivation, and improvement in vocabulary mastery. However, participants also mentioned drawbacks, such as Duolingo's inability to provide specialized Electromedical Engineering vocabulary, the use of fake images that hindered comprehension of meaning in real-life contexts, and the lack of interactivity in language skills assessment. The study recommends ESP practitioners to consider student-centered learning tools for assessing English proficiency, focusing on the test's purpose, objectives, practicality, reliability, validity, authenticity, and washback effects.